The taking of Jemima Boone [large type] : colonial settlers, tribal nations, and the kidnap that shaped America - Pearl, Matthew (Harper Large Print, an imprint of HarperCollinsPublishers, 2021)
Explores the little-known true story of the kidnapping of thirteen-year-old Jemima Boone, Daniel Boone's daughter, by a Cherokee-Shawnee raiding party and the ensuing battle with reverberations that nobody could predict.